DESKRIPSI PEMECAHAN MASALAH SISWA SMP DALAM MENYELESAIKAN SOAL TIMSS KONTEN ALJABAR - Sidauruk, Elsa Ernisa Valen; Ratu, Novisita (Universitas Muhammadiyah Semarang, 2018)
The aims of this research to describe the problem solving of students in solving the TIMSS algebra content problem with the topic is pattern based on the Polya stage for 8th grader students in SMP Negeri 3 Salatiga. This type of research is a qualitative descriptive. There are two questions about TIMSS algebra content with the topic pattern, with subject selection by purposive sampling obtained as many as 3 subjects. The result showed that is the matter of arithmetic number pattern for the subject S1 and S3 able to pass all the stages of Polya well, but for the subject S2 of the stages of Polya that were not carried out is check again. The pictorial pattern problem for the subject S1 as able to pass all the Polya stages well, but the subject S2 and S3 the Polya stage is not performed is check again.